Transformative Communication Radar: Practices, Action and Praxis Communication in Solidarity Economy Networks in Portugal and Catalonia - Sara Moreira; Cristina Parente (tripleC: Communication, Capitalism & Critique)
This article explores the transformational character of solidarity economy network communication in Portugal and Catalonia, focusing on the first two months of the crisis brought on by COVID-19. We assume that what these networks choose to convey (or remain silent on) in their public communications reflects their positions in the fields of action and values and their theoretical alignment, establishing an ethico-political orientation. Through the analysis of virtual content conveyed by solidarity economy organisations, we analyse the topics covered, the types of content and sources cited, and the level of demand in the discourse, as well as their individual, institutional and collective character. The results reveal very different communicative approaches in each of the cases analysed: from silence or total absence of communicative practices to what can be considered a transformational praxis communication, based on collective action challenging the structures of power and domination and pointing out ways to overcome them. The article proposes a transformative communication radar linking Habermas’s theory of communicative action and Fuchs’s Marxist-inspired praxis communication concept, as a way of distinguishing merely instrumental communicative approaches from those guided by communicative and cooperative rationality driving new agreements and societal transformations.